The role of bamboo shoots derived flavonoids as Epstein-Barr virus inhibitors in nasopharyngeal carcinoma - Widiantari, Ida Ayu Alit; Fatmawati, Ni Nengah Dwi; Nuaba, I. Gde Ardika; Suanda, I. Ketut; Lesmana, I. Wayan Lolik (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Epstein-Barr virus (EBV) is a ubiquitous oncogenic virus that infects humans and is strongly associated with various malignancies, including nasopharyngeal carcinoma (NPC), Hodgkin lymphoma, and B-cell lymphomas. One of the major challenges in the management of EBV-associated diseases is the virus’s ability to establish latency and evade host immune surveillance. Conventional treatments such as chemotherapy and radiotherapy are often unable to specifically target latent EBV reservoirs, highlighting the need for complementary therapeutic approaches. Bamboo shoots, a traditional dietary component, contain a variety of flavonoid compounds that have been shown to possess diverse biological activities, including antiviral and anticancer effects. This article aims to review the potential of flavonoid compounds found in bamboo shoots as anti-EBV agents in NPC based on evidence from previous studies. The review methodology involved a comprehensive search of scientific publications from reputable databases. The findings indicate that flavonoids such as luteolin, apigenin, and quercetin present in bamboo shoots exert inhibitory effects on the EBV life cycle by suppressing viral reactivation from the latent to the lytic phase, downregulating the expression of EBV latent proteins (LMP1 and LMP2A), and inducing apoptosis in EBV-infected cells. In conclusion, flavonoids derived from bamboo shoots demonstrate potential for development as adjuvant therapeutic agents in NPC by targeting EBV infection; however, further studies are required to establish their clinical efficacy.